Dugin’s deconstruction of postmodernity – postliberalism and postpolitics - Перишић, Срђан (Sociološki pregled, 2021)
The paper studies Dugin’s argumentation of postmodernity. In his philosophical and politicological works (Philosophy of Politics, Postphilosophy, Fourth Political Theory and Postmodern Geopolitics) written after 2000, Dugin applies the deconstruction method to explain the postmodern paradigm which the West definitely stepped into at the end of the twentieth century. We begin with his understanding of the end of modernism and revelation of liberalism as a matrix of the emergence of the postmodern paradigm. Afterwards we study the revelation of postmodern liberalism as postliberalism. Moreover, the question is analyzed as to how postmodernization of the liberal individual into the postindividual one proceeds. In the final considerations we speak of the transformation of modern politics into postpolitics.